Analisis Pengaruh Pemberian Posisi Semi Fowler 30 Derajat dan 45 Derajat terhadap Frekuensi Pernapasan pada Pasien TB PARU - Ayuni, Wulanda; Lutiyah, Lutiyah; Alamsyah, Azhar Zulkarnain; Hadiyanto, Hendri (Journal of Telenursing (JOTING), 2026)
This study aimed to analyze the effect of the 30-degree and 45-degree Semi-Fowler positions on respiratory rate in patients with pulmonary tuberculosis (TB). The method used was a quasi-experimental approach with a pre-post test. The results showed a significant effect (p-value 0.000) in the second position. Respiratory rate in the 30-degree position decreased from an average of 25 to 22 breaths/minute, while in the 45-degree position, the decrease was more effective, from 26 to 21 breaths/minute. The 45-degree position proved more optimal in reducing shortness of breath because it maximizes the force of gravity to reduce pressure on abdominal organs against the diaphragm, resulting in maximum lung expansion. In conclusion, the 45-degree Semi-Fowler position is more effective in stabilizing respiratory rate in patients with pulmonary tuberculosis than the 30-degree position.   Keywords: Respiratory Rate, Breathing Pattern, Semi-Fowler, Pulmonary TB